Cerebral infarct and meningitis secondary to Lemierre's syndrome - Bentham, JR; Pollard, A; Milford, C; Anslow, P; Pike, MG (2004)
The case is reported of a young man with Fusobacterium necrophorum septicemia who developed cavernous sinus thrombosis, meningitis, carotid artery stenosis and stroke. This article presents the only reported case of arterial stroke in Lemierre's syndrome. Clinical presentation, diagnostic difficulty and treatment are discussed. © 2004 by Elsevier Inc. All rights reserved.